Bicycling for transportation : an evidence-base for communities - Bopp, Melissa; Sims, Dangaia; Piatkowski, Daniel (Elsevier, 2018)
Biking for Transportation: A Public Health and Behavior Perspective examines the individual and societal factors of active transportation and biking behavior. The book uses an Interdisciplinary approach to provide a comprehensive overview of bicycling for transportation research. It examines the variability in biking participation among different demographic groups and the multiple levels of influence on biking to better inform researchers and practitioners on the effective use of community resources, programming and policymaking. It is an ideal resource for public health professionals trying to encourage physical activity through biking. In addition, it makes the case for new infrastructure that supports these initiatives.